Influence of Selection Options on the Color and Turn of Karakalpak Sur Lambs - Abdirazakovich, Urimbetov Akhmet (American Journal of Botany and Bioengineering, 2025)
The article highlights research materials in the direction of studying the characteristics of the manifestation of certain indicators of colors and curls in lambs, depending on different options for selecting parents according to colors. Similarities and differences in the manifestation of the studied indicators have been established.